Decision Tree Model for Classifying University Students Eligible for UKT Waivers - Gde Yoga Agastyar Priatdana (INFOTEKS (Information Technology, Computer and Sciences), 2024)
This paper develops a Decision Tree-based classification model to determine student eligibility for UKT (Single Tuition Fee) waivers using socio-economic factors such as parental income, household type, parental occupation, number of dependents, and vehicle ownership. The goal is to automate the identification of students qualifying for financial aid, improving efficiency and fairness in resource allocation. The model was trained on a dataset containing both categorical and numerical features, with the target variable being binary: